CHINA`'S «SOFT POWER» POLICY: «ONE BELT ONE ROAD» INITIATIVE AND EGYPT. FIRST PHASE OF ABD AL FATTAH AL SISSI'S PRESIDENCY (Journal of Oriental Studies, 2024)
For a long time, the main political movers and shakers across the Middle East and North Africa (hereinafter - MENA) traditionally were the countries of the so-called Anglo-Saxon world, more specifically the United States was the most active global player. The Soviet Union was competing fiercely with the Western world for the influence in that regions. Since the collapse of the Soviet Union, the Russian Federation, partially has lost its traditional influence as bipolar system of international relations was eroding. After the end of the "Cold War", the USA, the European Union, and to some extent the Russian Federation, continued to maintain their presence in MENA region, but the situation gradually began to change in the 2000s.  China had a relatively low involvement in the MENA region, however, due to its rapid economic development, initiated a new strategy of establishing relations with energy-rich Middle Eastern and North African countries. Through these new strategy in the MENA region, China tried to ensure its energy security. China began to implement the "dialogue of building warm relations" with the countries of the above-mentioned regions through "soft power". The policy of "soft power" implemented by China in modern international relations is unique and extremely interesting in terms of its ideological base and toolkits. The effectiveness of implementing soft power policies often makes official Beijing one of the most influential actors in the Arab world. This article, is an attempt to present the concept of Chinese "soft power" and the example of its implementation in the light of Egyptian-Chinese relations.
Keywords: China; Egypt; Soft Power; «One Belt One Road»; Regional Cooperation; Peace and Security; PowerըEconomic Cooperation